Representations of violence against women in the chilean press - Olivares Ramirez, Yanira (Re-presentaciones: Periodismo, comunicación y sociedad, 2019)
This article focuses on the frames that the media give to events of violence against women in Chile. For this, the research offers a content analysis to the Chilean press, focusing on the information treatment and media coverage given to the frustrated feminicide against Nabila Rifo, fact occurred in 2016. A great coverage and relevance to the case was observed, which suggests a positioning of violence against women in the Chilean media agenda. However, the informative treatment showed several shortcomings (epistemological ruptures, absence of context, overexposure of the victim, motives and justifications, poor incorporation of specialized sources in the subject, scarce educational information, morbid frames, among others). Consequently, it is proposed that, despite the visibility of the issue, the information treatment in the Chilean press uses approaches that do not incorporate a gender perspective, facilitating a second space of violence for the victim.